2011
DOI: 10.1007/s11605-011-1490-1
|View full text |Cite
|
Sign up to set email alerts
|

Linear Stapled Esophagogastrostomy is more Effective than Hand-Sewn or Circular Stapler in Prevention of Anastomotic Stricture: a Comparative Clinical Study

Abstract: The linear stapled esophagogastrostomy could decrease anastomotic stricture without increasing gastroesophageal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 24 publications
0
34
0
2
Order By: Relevance
“…The application of endoscopic linear stapler for CEGA has effectively reduced anastomotic complications compared to conventional hand-sewn anastomosis [46, 9]. Several studies showed that linear stapled technique had a lower frequency of anastomotic stenosis than CSA [8, 11, 18]. The DSA technique has been reported since 2005 [13].…”
Section: Discussionmentioning
confidence: 99%
“…The application of endoscopic linear stapler for CEGA has effectively reduced anastomotic complications compared to conventional hand-sewn anastomosis [46, 9]. Several studies showed that linear stapled technique had a lower frequency of anastomotic stenosis than CSA [8, 11, 18]. The DSA technique has been reported since 2005 [13].…”
Section: Discussionmentioning
confidence: 99%
“…They have shown better performance for the linear anastomosis [23,24], but this lower rate of anastomotic stricture seemed to be gauged by a higher anastomotic diameter in the linear arms of those studies rather than the superiority of linear method over circular one. For example, Xu et al compared a group of 166 patients who underwent esophagogastrostomy with the linear stapled method with 68 subjects who underwent the same surgery with the circular stapled technique and demonstrated a significantly higher rate of anastomotic stricture in the circular stapled group compared with the other linear stapled group (20.9% vs 1.9%; P  < 0.001) [24]. This could be related to a significantly higher mean diameter of the anastomotic orifice in the linear group compared with the circular arm (1.6 vs 1.0 cm).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure should be as fast as possible, with the least tissue trauma and quick restoring function, and, consequently, minimization of the possibility of postoperative complications. 1,2 It was only in the late 19th century, however, that gastrointestinal sutures became reliable, due to an acquired knowledge of the principles of …”
Section: Introductionmentioning
confidence: 99%
“…The cost of using a stapler is high, and its indication should be based on the real advantages of its use. 2,3,10 It is of great importance to the final outcome of sutures, be they done manually or mechanically, to take care in all processes, such as with hemostasis, dissection and suitable preparation of the edges to be sutured, blood supply, and lack of tension in the suture line. 10,11 Accordingly, the literature has proven that there are no substantial differences in the end results of manual sutures and those made by staplers.…”
mentioning
confidence: 99%
See 1 more Smart Citation